Burnout phenomenon still unresolved. The current state in theory and implications for public interest - Mańkowska, Beata (Frontiers in Organizational Psychology, 2025)
Occupational burnout currently poses one of the greatest threats to professionally active individuals. Despite nearly 50 years of research on the phenomenon, its complex mechanisms are still under investigation. The lack of agreement among scholars in this regard makes it challenging to accurately diagnose the problem and effectively prevent it. The aim of this article is to delineate commonalities and differences among leading researchers who have been engaged in a longstanding debate about the nature of burnout. The criticisms presented serve as a provocation aimed at mobilizing and uniting scientific communities to deepen their understanding of the essence, mechanisms, and accurate diagnostic methods of this pressing issue. These topics are crucial for the public interest and wellbeing of citizens worldwide.